Interactive Learning Media Development Based on Google Sites in Subjects Science Junior High School - Citra Wulandari; Fetri Yeni; Abna Hidayati; Ulfia Rahmi (Postgraduate, University of Mataram, 2025)
This research is motivated by the need for digital-based interactive learning media that supports junior high school students' understanding of science concepts. The purpose of this study is to develop Google Sites-based learning media and measure its validity, practicality, and effectiveness in improving learning outcomes. The study uses a Research and Development (R&D) approach with the ADDIE model, including the stages of analysis, design, development, implementation, and evaluation. The research subjects were teachers and eighth-grade students. The instruments used included expert validation sheets, teacher and student practicality questionnaires, and learning outcome tests. Data were analyzed descriptively for validity and practicality, and used a Paired Sample T-Test to test effectiveness. The results showed that the media obtained a validity score of 87%, teacher practicality 90%, and student practicality 92%. Learning outcomes increased from 55.7% (pretest) to 78.6% (posttest) with a significance value of 0.032 (p < 0.05). In conclusion, this Google Sites-based learning media is valid, practical, and effective, and is suitable for use to improve junior high school students' understanding of science concepts in an interactive and interesting manner.